Study on the correlation between basketball players` multiple-object tracking ability and sports decision-making - Gou, Q.; Li, S. (PLOS ONE, 2023)
Background Players` multiple-object tracking (MOT) ability is very important in basketball because it may affect players` sports decision-making (SDM), thus affecting the results of the game. The purpose of this study was to investigate the differences between expert and novice basketball players in MOT ability and SDM and to explore the correlation between basketball players` visual attention and SDM. Methods A total of 48 female basketball players (24 categorized in the expert group and 24 in the novice group) participated in the MOT task in Experiment 1 and the basketball 3 vs. 3 games in Experiment 2. Experiment 1 examined the difference in dynamic visual attention characteristics between expert players and novice players by changing the tracking number. Experiment 2 examined the differences between expert players and novice players through the SDM of basketball 3 vs. 3 games. Sports decisions were evaluated by basketball experts. MOT ability and SDM ability were analyzed through Pearson correlation. Results The overall MOT accuracy of expert players (64.6%) and novice players (55.7%) was significantly different (?2 = 59.693, P = 0.000). There was no significant difference in accuracy when tracking 2-3 targets (P > 0.05), but there was a significant difference in accuracy when tracking 4-6 targets (P < 0.05). The overall SDM accuracy of expert players (91.6%) and novice players (84.5%) was significantly different (?2 = 31.975, P = 0.000). There was no significant difference between expert players and novice players in the accuracy of dribbling decision-making (P > 0.05), but there was a significant difference in the accuracy of passing decision-making and shooting decision-making (P < 0.01). When tracking 4-5 targets, the tracking score was positively correlated with the passing decision score and dribbling decision score of expert players, and the tracking score of novice players was positively correlated with the passing decision score (r > 0.6, P < 0.01). Conclusions First, the tracking accuracy of expert players was significantly higher than that of novice players, especially when tracking 4-6 targets. As the number of targets increased, accuracy decreased. Second, the accuracy of expert players` SDM was significantly higher than that of novice players, especially in passing decision-making and shooting decision-making. Expert players exhibited fast and accurate SDM. Third, there was a correlation between MOT ability and SDM performance. The MOT ability of 4-5 targets was positively correlated with passing decision-making, which was statistically significant. The correlation between the MOT ability and SDM performance of expert players was greater and more significant. Having too many targets to track (more than 6) interfered with players` decisions.